KAJIAN TINGKAT AKURASI DAN KETELITIAN GEOMETRI PETA DASAR DARI HASIL PENGOLAHAN DATA FOTO UDARA UNTUK PEMANFAATANNYA DI SEKTOR PERTAMBAGAN - Pangeran S. Panjaitan; Jance Murdjani Supit (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
Orthophoto is an aerial photo with a photographic recording process with the support of a detector or a film detector that has corrected its geometric errors using Digital Elevation Model (DEM) data. DEM data is a digital elevation model that represents the surface topography and Ground Control Point (GCP) or ground control points as a location point that is known or identified in real space on the ground surface. This can be used for mapping purposes without any scale inconsistencies throughout the photo coverage, and for getting a high-resolution scale map, that is corrected referring to geometric accuracy, which aims to be utilized in the mining sector as a base map on a large scale. From the results of the aerial photo data processing, the geometric accuracy of class I is at a scale of 1:500, which is used as a base map for the Mining Permit.